EVALUASI KEBIJAKAN OPERASIONAL SATUAN POLISI PAMONG PRAJA - Desheriyanto ' (Universitas Riau, 2016)
Evaluation of the Operational Policy Civil Service Police Unit. This study aims to determine the operational policy evaluation Civil Service Police Unit in the city of Pekanbaru. This research is a qualitative descriptive study. The informants are Kabid Trantib, members of municipal police, traders and the public. Data collection techniques used in this study was the observation of interviews and documentation. The results showed that the implementation of the operational police civil service in the policing of street vendors in the city of Pekanbaru masihbelum optimal, it can be seen from the effectiveness achieved, efficient use of resources, adequate to the solutions provided to traders and problems resposivitas field officers and accuracy against the benefits gained. Factors that constrain the implementation of operational policy of the civil service police unit in the city of Pekanbaru is the dissemination to the public of the rules in force, availability of resources, the attitude of enforcement agents in the field and support from the community.